Association between the C-reactive protein–albumin–lymphocyte index and metabolic syndrome: evidence from the 2003–2010 national health and nutrition examination survey - Lanlan Wu; Dunzheng Han; Yuting Xue; Shangfei He; Zhuang Ma; Shuwen Su; Peixin Li; Shenrong Liu; Haobin Zhou (Diabetology & Metabolic Syndrome)
Abstract Background Metabolic syndrome (MetS) is a global public health problem that significantly impacts human health and quality of life. The relationship between MetS and the C-reactive protein–albumin–lymphocyte (CALLY) index is uncertain. Methods This study analyzed the data of 7,534 individuals from the National Health and Nutrition Examination Survey cycles (2003–2010 cycles). Weighted logistic regression and weighted restricted cubic spline (RCS) curve analyses were used to identify the relationships between the CALLY index and MetS, as well as its components. Results Of the 7,534 participants, 2,086 were diagnosed with MetS. The estimated prevalence of MetS decreased with an increase in the CALLY index (P < 0.001). Multivariable logistic regression analysis showed that the odds ratio of MetS was 0.25 (95% confidence interval 0.20–0.32, P < 0.001) in the highest CALLY index quartile compared with the lowest quartile after adjusting for confounding variables. The RCS curve analysis revealed non-linear relationships between the CALLY index and MetS or its components. Conclusions This study revealed an inverse relationship between the CALLY index and MetS risk. The CALLY index might be valuable for identifying individuals who are at a high risk of MetS. Clinical trial number Not applicable.